2010
DOI: 10.4103/0253-7613.71889
|View full text |Cite
|
Sign up to set email alerts
|

Effect of calcium on anxiolytic activity of diazepam and verapamil in rats

Abstract: Objective:To analyze the role of calcium in anxiety and its effect on anxiolytic activity of diazepam and verapamil.Materials and Methods:Study was conducted using female albino rats in light and dark arena; a nonconflicting animal experimental model for anxiety. Animals were divided into six groups with six animals in each group. Test drugs, calcium gluconate (10 mg/kg), diazepam (1 mg/kg), verapamil (5 mg/kg), calcium + diazepam, and calcium + verapamil were administered intraperitoneally. Percentage of time… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…In India, the prevalence rate of anxiety disorders is 18.5 per 1000 population. (Hiremath et al, 2010) Anxiety issue need aid the practically normal for mental wellbeing issues. It is assessed that they in luence more or less 1 by 10 individuals.…”
Section: Introductionmentioning
confidence: 99%
“…In India, the prevalence rate of anxiety disorders is 18.5 per 1000 population. (Hiremath et al, 2010) Anxiety issue need aid the practically normal for mental wellbeing issues. It is assessed that they in luence more or less 1 by 10 individuals.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have demonstrated that acute and chronic administration of Mg reduces immobility time in the forced swimming test (FST) in mice and rats, and enhances the anti-immobility activity of imipramine in this model [11]- [13]. Effects of other bivalent cationic metals such as calcium [14] and zinc [15] on anxiety have been also investigated, although their results showed preliminary anxiolytic effects. However, magnesium has been among the most predominant metal in central nervous system to affect neurotransmission.…”
Section: Introductionmentioning
confidence: 99%